Association and benefits of 24-h activity behavior and academic procrastination among Chinese college students based on the isotemporal substitution model - Kuai, Fang; Wu, Xia; Zhou, Xiaoming; Liu, Wenxiang (Frontiers in Public Health, 2025)
ObjectiveThis study systematically explores the association between 24-h activity behaviors and academic procrastination among college students, with a focus on analyzing the influence mechanisms of different activity types and time allocation patterns on academic procrastination. The aim is to reveal the potential role of optimizing activity behavior patterns in alleviating academic procrastination and provide a scientific basis for campus health promotion strategies.MethodsData on 24-h activity behaviors (physical activity, sedentary behavior, sleep) and academic procrastination were collected from 986 college students through a questionnaire survey. Compositional data analysis was used to quantify the isotemporal substitution effects of activity behaviors, and dose–response analysis was combined to explore the dynamic relationship between activity time allocation and academic procrastination.Results(1) Academic procrastination was prevalent (52.5%) and significantly negatively correlated with academic performance (B = −2.85, p < 0.01) and mental health (β = −3.10, p < 0.01). (2) Physical activity levels were significantly negatively correlated with academic procrastination (β = −3.21, p < 0.001). Replacing sedentary behavior (SB) with moderate-to-vigorous physical activity (MVPA) was associated with a 0.79-unit reduction in the total score of academic procrastination (95%CI: −1.25 to −0.33). (3) Dose–response analysis of time substitution showed that the improvement benefit of academic procrastination was highly effective within the first 20 min of substitution; for instance, when MVPA replaced SB for 20 min, the total score decreased by 0.47 units, suggesting that 20 min may be a critical time window for behavioral intervention.ConclusionAcademic procrastination among college students is closely related to activity behavior patterns. Higher MVPA time and lower SB are associated with significantly lower levels of procrastination, suggesting that optimizing daily activity allocation may be a viable strategy for intervention. It is recommended to formulate targeted intervention strategies by optimizing daily activity time allocation (e.g., adding 20 min of MVPA daily to replace SB) to provide scientific guidance for promoting the physical and mental health of college students.